2019
DOI: 10.1021/acs.chemmater.8b05259
|View full text |Cite
|
Sign up to set email alerts
|

Managing Local Order in Conjugated Polymer Blends via Polarity Contrast

Abstract: The optoelectronic landscape of conjugated polymers is intimately related to their molecular arrangement and packing, with minute changes in local order, such as chain conformation and torsional backbone order/disorder, frequently having a substantial effect on macroscopic properties. While many of these local features can be manipulated via chemical design, the synthesis of a series of compounds is often required to elucidate correlations between chemical structure and macromolecular ordering. Here, we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 54 publications
1
22
0
Order By: Relevance
“…To give an example, the glass transition temperature, T g , of poly[3‐tetra(ethylene glycol)thiophene]—a material comprised of a polythiophene backbone and oligo(ethylene glycol) side chains—is notably affected by exposure to a humid environment. [ 13 ] In turn, the torsional backbone order and, hence, optoelectronic features significantly vary with temperature. [ 13 ] Structural [ 14 ] and mechanical properties also will be affected, rendering systematic establishment of structure/property relations intricate.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…To give an example, the glass transition temperature, T g , of poly[3‐tetra(ethylene glycol)thiophene]—a material comprised of a polythiophene backbone and oligo(ethylene glycol) side chains—is notably affected by exposure to a humid environment. [ 13 ] In turn, the torsional backbone order and, hence, optoelectronic features significantly vary with temperature. [ 13 ] Structural [ 14 ] and mechanical properties also will be affected, rendering systematic establishment of structure/property relations intricate.…”
Section: Figurementioning
confidence: 99%
“…[ 13 ] In turn, the torsional backbone order and, hence, optoelectronic features significantly vary with temperature. [ 13 ] Structural [ 14 ] and mechanical properties also will be affected, rendering systematic establishment of structure/property relations intricate. In this communication, we demonstrate that in poly[3‐(6‐hydroxy)hexylthiophene] (P3HHT, see inset in Figure a for chemical structure), hydroxylated alkyl side chains introduce mixed conduction when operated with aqueous electrolytes, as work on random copolymers of poly(3‐hexyl thiophene) (P3HT) and P3HHT already indicated, [ 15 ] but without excessive swelling and/or unwanted plasticizing effects observed in materials with oligoethylene‐glycol side chains.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…for a polythiophene with tetraethylene glycol side chains blended with poly(ethylene oxide). [ 33 ] For the lowest measured composition of c P3HT = 0.0005 wt% the PL emission spectrum shows both features of aggregated and nonaggregated P3HT. It can be concluded that the conjugated polymer partially aggregates even at low compositions c P3HT < 0.01 wt%, which approach the monotectic composition, albeit likely as a single, self‐aggregated chain due to the high degree of dilution in LDPE.…”
Section: Resultsmentioning
confidence: 99%
“…This mode red-shifts during the first redox process (SI Figures S14, S16), representing a relaxation of the Cα=Cβ(-O) bond as it adopts a more single-bond character. In P3HT films, a shifting of this mode to lower frequencies has been attributed to greater torsional order and enhanced delocalization of π-electron, which again suggests that the early stages of doping are characterized by enhanced chain planarity [59][60][61]. Similarly, mode 9 (~1515 cm -1 , corresponding to the Cα=Cβ(-O) asymmetric stretch) also red shifts upon the initial oxidation of the polymer and then blue-shifts after the onset of the second redox process (SIFigureS12, S13).…”
mentioning
confidence: 99%